2017
DOI: 10.1038/s41598-017-15071-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and cellular oxidant production induced by naphthalene secondary organic aerosol (SOA): effect of redox-active metals and photochemical aging

Abstract: Exposure to air pollution is a leading global health risk. Secondary organic aerosol (SOA) constitute a large portion of ambient particulate matter (PM). In this study, the water-soluble oxidative potential (OP) determined by dithiothreitol (DTT) consumption and intracellular reactive oxygen and nitrogen species (ROS/RNS) production was measured for SOA generated from the photooxidation of naphthalene in the presence of iron sulfate and ammonium sulfate seed particles. The measured intrinsic OP varied for aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 93 publications
6
73
1
Order By: Relevance
“…Finally, the multiple model result for the GSH assay should be considered with caution since a normal distribution was not reached in the first step of the analysis. Moreover, multiple nonlinear regression models should also be investigated since several studies have shown that oxidative potentials from different PM components are not always additive (Tuet et al, 2016(Tuet et al, , 2018Wang et al, 2017;Xiong et al, 2017;Yu et al, 2018). Finally, these analyses are only relevant for PM 10 when some health studies are now taking PM 2.5 into account.…”
Section: Multiple Linear Regression Modelsmentioning
confidence: 99%
“…Finally, the multiple model result for the GSH assay should be considered with caution since a normal distribution was not reached in the first step of the analysis. Moreover, multiple nonlinear regression models should also be investigated since several studies have shown that oxidative potentials from different PM components are not always additive (Tuet et al, 2016(Tuet et al, , 2018Wang et al, 2017;Xiong et al, 2017;Yu et al, 2018). Finally, these analyses are only relevant for PM 10 when some health studies are now taking PM 2.5 into account.…”
Section: Multiple Linear Regression Modelsmentioning
confidence: 99%
“…Since the composition of the atmospheric particulate matter (PM) depends on the sources and their chemical transformation in the atmosphere, an important question is which PM constituents are responsible for the adverse human health effects. Sulfate, organic carbon (OC), and transition metals have been shown to be more prominently associated with adverse health outcomes than other pollutants (Lippmann et al, 2013;Adams et al, 2015;Vedal et al, 2013;Burnett et al, 2000), even though there is no toxicological evidence supporting a causal role (WHO, 2013b). It is generally hypothesized that the adverse health effects caused by PM largely derive from oxidative stress induced by reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…Different acellular assays have been explored to characterize the oxidant activity of PM. For instance, the 2 ,7 -dichlorofluorescin (DCFH) and the p-hydroxyphenylacetic acid (POHPAA) assays respond to a range of organic peroxides (Venkatachari and Hopke, 2008;Wang et al, 2011a;King and Weber, 2013;Zhou et al, 2018a;Hasson and Paulson, 2003) and are used to measure particle-bound ROS (PB-ROS). Similarly, the assay with 9,10-bis (phenylethynyl) anthracene nitroxide (BPEA-nit) measures the amount of PB-ROS, including radicals and metals such as Cu + and Fe 2+ , but not the ROS generated from Fenton chemistry (Miljevic et al, 2010;Hedayat et al, 2016).…”
mentioning
confidence: 99%
“…Various experiments have also shown that pure SOA does induce adverse effects upon exposure of airway epithelial cells (Arashiro et al, 2016(Arashiro et al, , 2018Gaschen et al, 2010;Lin et al, 2016;Chowdury et al, 2018;Jiang et al, 2016). Similarly, cellular based ROS assays show a strong connection with pure SOA or its fraction in PM (Tuet et al, 2016;Tuet et al, 2017a;Tuet et al, 2017b;Saffari et al, 2014). Further, Lakey et al (2016) developed a model to simulate the response of air pollutants including PM on the production rates and concentrations of ROS in the epithelial lining fluid of the human respiratory tract.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%